'Got my own world to live through': race and categorisation in Jimi Hendrix's music - Bradshaw-Hughes, Matthew (2020)
Jimi Hendrix and his music have been continuously subjected to racial classification by critics who have chosen not to look at Hendrix’s own views on race in sufficient detail or context. Given that Hendrix himself rejected the framework of racial classification, this thesis explores the strengths and weaknesses of a racial analysis of his music by looking at it from the perspective of two relatively recent critical-aesthetic discourses, Afrofuturism and Afrosurrealism. While they are interesting and productive in some ways, these approaches do not fully account for Hendrix’s thematic concerns and unique aesthetic approach which demonstrates how sound in particular is not reducible to race.